Liposarcoma of tongue: A case report - Amarjot Kaur; Aminder Singh; Vikram Narang; Chandan Kakkar (Indian Journal of Pathology and Microbiology)
Liposarcoma (LS) is one of the most common malignant tumors. However, oral LS is an extremely rare lesion that is often clinically misdiagnosed as a benign lesion because of its asymptomatic and indolent clinical course. In oral cavity, the tongue is the most frequent site for its occurrence.